How Adolescents Cope with Technostress: A Mixed-Methods Approach. Issue 2 (3rd April 2021) - Schmidt, Marco; Frank, Lukas; Gimpel, Henner
ABSTRACT: A broad stream of research strives to understand stress directly or indirectly resulting from the use of information and communication technology (ICT), commonly referred to as technostress. A group at high risk of suffering from the consequences of technostress is adolescents because they grow up using ICT daily and are still developing their identity, acquiring mental strength, and adopting essential social skills. Our research combines a qualitative and a quantitative study and contributes to an understanding of what strategies adolescents use to cope with the demands of ICT use. In qualitative workshops with adolescents, we collect 30 coping responses in five categories. A subsequent quantitative study finds gender- and age-related differences in adolescents' perception of technostress and concludes that adolescents as a group activate a broad portfolio of coping responses. Exploratory factor analysis reveals five factors underlying adolescents' activation of coping responses: Avoid Stressful ICT, Follow the Rules, Use ICT Consciously, Contain Negative Emotions, and Acquire ICT . We find that the coping responses related to the Avoid Stressful ICT factor are significantly more common among girls than boys and derive that adolescents who own more devices might have a lower tendency to Follow the Rules . A joint analysis of coping responses and technostress creators reveals that, not surprisingly, coping increases with higher intensity of technostress, but some coping responses break out of this pattern. With this research, we contribute to the theoretical and empirical understanding of an important phenomenon associated with digitalization's dark sides (technostress coping) in an important yet understudied population (adolescents 10–17 years of age). Future research may build on our work and investigate additional parameters determining differences in adolescents' coping behavior.